AMS radiocarbon data of organic material from the ice wedges and paleo-winter temperature reconstructions obtained from stable water isotope records of the Batagay syngenetic ice wedges - Yurij K Vasil extquotesinglechuk; Jessica Yurevna Vasil extquotesinglechuk; Nadine A Budantseva; Alla Constantinovna Vasil extquotesinglechuk (PANGAEA, 2024)
The Batagay megaslump is the largest one on the Earth and located close to the Batagay settlement on the right bank of the Yana River in Yakutia, eastern Siberia. Radiocarbon data were obtained to verify the formation time of ice wedges in the Upper Ice Complex of the Batagay yedoma. Furthermore, a cryostratigraphic description and the detailed vertical distribution of the δ18O, δ2 H, and dexc values of the three studied ice wedges is provided. The 14 dates obtained from the ice wedges allowed to date the formation time of studied ice wedges in the Upper Ice Complex from 47.9 to 27.2 cal ka BP. Based on the stable isotope record (171 samples), the average January temperature during the Late Pleistocene was consistently low at -51 for both periods from 30.800 to 27.100 cal BP - Marine Isotope Stage (MIS 2) and from 47,900-44,700 cal BP (MIS 3) in the Verkhoyansk district of Yakutia.